2017
DOI: 10.1038/s41598-017-00741-4
|View full text |Cite
|
Sign up to set email alerts
|

Systemic frequencies of T helper 1 and T helper 17 cells in patients with age-related macular degeneration: A case-control study

Abstract: Age-related macular degeneration (AMD) is a degenerative disease of the retina and a leading cause of irreversible vision loss. We investigated the systemic differences in the frequency of T helper (Th) 1 and Th17 cells in patients with non-exudative and exudative AMD and compared to age-matched controls. Flow cytometry was used to determine the systemic frequency of Th1 (CD4+CXCR3+IL12RB2+) and Th17 (CD4+CCR6+IL23R+) cells, and percentage of CD4+ T-cells expressing CXCR3, IL12RB2, CCR6, IL23R, and co-expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 53 publications
2
34
0
Order By: Relevance
“…SJ-142, SJ-379, and SJ-385) and adhered to the tenets of the Declaration of Helsinki. Blood samples from some of the participants were used for studies of aging and age-related macular degeneration [69]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SJ-142, SJ-379, and SJ-385) and adhered to the tenets of the Declaration of Helsinki. Blood samples from some of the participants were used for studies of aging and age-related macular degeneration [69]. …”
Section: Methodsmentioning
confidence: 99%
“…Physical activity was evaluated using a yes/no survey question for epidemiological studies as proposed by Schechtman et al [11]: Do you currently participate in any regular activity or program (either on your own or in a formal class) designed to improve or maintain your physical fitness? We translated this question using forward and backward translation [10], and have previously validated its use in elderly Danes [9,12]. Smoking habits were categorized into ever or never smokers, as this was considered a more robust measure towards both recall bias (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 These infiltrating cells and the broad alterations of systemic immune cells suggests the involvement of the adaptive immune system in AMD and supports the notion of AMD as a systemic disease. In patients with neovascular AMD we previously found neutrophils with an altered activation state, 12 lower frequency of T-helper 1 cell 13 and aged phenotype of cytotoxic T-cells. 14 Furthermore, natural killer cells are demonstrated to promote CNV formation, 15 and B cells from donors with AMD tend to be more sensitive to antigen-stimulation.…”
Section: Introductionmentioning
confidence: 88%
“…Participants were recruited consecutively from our outpatient clinic at Department of Ophthalmology, Zealand University Hospital, Denmark. Based on our previous study on CD4 þ CXCR3 þ CCR6 þ T cells in patients with neovascular AMD, 17 we calculated that at least 18 participants in each group was necessary to obtain sufficient power (assuming a ¼ 0.05, b ¼ 0.8, and r ¼ 2). Therefore, we recruited at least 18 participants in each group and stopped further recruitment after a total of 110 participants.…”
Section: Study Design and Ethicsmentioning
confidence: 99%
“…Studies of experimental CNVs on mice and observational studies in patients with neovascular AMD suggest that blood leukocytes are important for CNV formation. [15][16][17][18][19][20][21][22][23] Lechner et al 20 found that complement proteins C3a, C4a, and C5a were significantly increased in plasma of patients with neovascular AMD, but not in patients with PCV. Liu et al 21 found that complement protein C5a promotes CD4 þ T cell expression of IL-17 and IL-22.…”
mentioning
confidence: 99%